Editorial: Observed and Predicted Changes in Climate in the Andes Cordillera - Masiokas, Mariano Hugo (2020)
The Andes Cordillera forms a continuous high elevation range along the western margin ofSouth America and constitutes a fundamental component in the environmental, cultural, andsocio-economic fabric of the continent. Over its ca. 7,000 km-long extent, this mountain rangecontains an immense variety of climates and biomes and provides natural resources and ecosystem services to a population of almost 100 million people in Venezuela, Colombia, Ecuador, Peru, Bolivia, Chile, and Argentina.Over the past decades various ecological, glaciological, and hydrological assessments haveidentified noticeable changes in vegetation dynamics, glacier cover and water availability indifferent sectors of the Andes. Although these findings can be at least partially associated withthe occurrence of warmer and/or drier conditions across the Andes, additional, more detailedclimatological assessments are needed to improve understanding of the complex patterns of climate change that have occurred in recent decades across this extensive mountain range. Given the predominant role of the Andean climate system on many socio-economic activities and on themost important hydrological and ecological processes in this region, further detailed studies arealso needed to identify the most likely future climate scenarios for high elevation areas at differentlatitudes in the Andes. This Frontiers Research Topic compiles, in only a few studies, a greatdiversity of innovative meteorological, climatological, and glaciological analyses in different sectorsof the Andes from Colombia to southern Chile and Argentina.